KAJIAN EFEKTIFITAS PENGHAMBATAN NITRIFIKASI PADA RHIZOSPHERE BERBAGAI SPESIES TANAMAN Brachiaria DI ALFISOLS - Anastasia Intan Sawitri; Purwanto Purwanto; Slamet Minardi (Faculty of Agriculture, Universitas Sebelas Maret, 2013)
Title : Study on Effectiveness of Nitrification Inhibition in Rhizosphere of Brachiaria species on Ultisol. It has been known for some plant species Brachiaria (Brachiaraia decumbens, Brachiaria humidicola , and Brachiaria brizantha ) that have been studied has been hoen to effectively inhibit nitrification from that rhizosphere activity. Therefore it is necessary to further resarch the cultivation of other plant Brachiaria species such as Brachiaria mutica , Brachiaria decumbens and Brachiaria humidicola, to determine the effectiveness as a barrier to the rate of nitification that carried out by the method of pot experiments with functional relationship variables approach based on sampling and nondestructif Completely Randomized Design ( CRD ) consisting of plant species Brachiaria factor . and various doses of N fertilizer is 100 kg / ha , 150 kg / ha , 200 kg / ha . Results of this study indicate that 1 ) Brachiaria mutica , Brachiaria decumbens and Brachiaria humidicola , very significant on nitrification potential , but the treatment of a wide range of doses of fertilizer N is not a real effect on nitrification potential . 2 ) Highest nitrification potential value in the treatment Brachiaria mutica in the amount of 5,114 mg NO2- / g soil /5hour , while the lowest value of the potential nitrification in plants Brachiaria humidicola is equal to 0,414 mg NO2- / g soil /5hour . 3 ) Of the three treatment plants Brachiaria sp . in that the treatment plant can Brachiaria humidicola considered the most effective in inhibiting nitrification.